(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To determine the frequency of UTI in neonates presenting with sepsis and to identify the causative organisms. Place and duration: Department of Neonatology Fatima Memorial Hospital Lahore. Out of first 3000 neonates delivered in FMH from July - December 2009, newborn suspected of sepsis were included in the study. Patient and method: The study was conducted in year 2009. This was a prospective study. Data was collected from neonatal unit of Fatima Memorial Hospital.3000 newborns delivered from July-December2009 were included in study .Informed consent was taken and confidentiality of data was ensured. Urine cultures were done in all the cases with suspected sepsis. Results: Out of 3000 newborns 339 were investigated for sepsis and UTI was found in11% cases of suspected of sepsis. Most common organism was E.Coli (40%), Klebsiella (32%) and other organisms included Acinetobacter, Enterobacter and Pseudomonas. Conclusion: UTI is found in 1.23% of newborns delivered in FMH. In cases of suspected sepsis it accounted for 11% cases and most common organism being E.COLI.